Acute compartment syndrome of the foot due to a twisting injury while playing sports. Issue 10 (30th October 2020) - Hijazi, Humayun; O'Reilly, Marc; Moloney, Darren Patrick; Bayer, Thomas
Abstract : Acute compartment syndrome (ACS) of the foot is one of the most severe injuries of the foot and typically results from a fracture, crush or vascular injury. ACS, isolated to a single foot compartment, is a rare complication following a simple twisting injury of the ankle. In this article, the authors present the case report of a 25-year-old man who developed ACS, isolated to the lateral compartment of the foot, secondary to rupture of the lateral ligament complex and subsequent haematoma formation. An emergency fasciotomy was performed and the patient had complete resolution of his symptoms. ACS is usually associated with significant trauma, however, there are reported cases in the literature associated with a minor injury. In this case report, the authors describe how ACS developed following a simple ankle sprain playing sports in the absence of a high-energy insult or fracture.